APPLICATION OF PACKING THEORY ON GRADING DESIGN FOR POROUS ASPHALT MIXTURES - Hardiman Hardiman (Civil Engineering Dimension, 2004)
The design life of porous asphalt is shorter than dense mix as a consequence of permeability loss due to clogging and poor resistance to disintegration. To mitigate problems associated with clogging, double layer porous asphalt has been constructed in the Netherlands. This paper investigated a development of a new grading design for porous asphalt by varying percentage of aggregate with maximum sizes of 20, 14 and 10mm; a theory of packing was used. The most common method used for grading design is based on empirical, which does not relate the packing behaviour of the aggregate mass. The packing theory used in this study was facilitated by a vibratory compactor. It was found that mixtures containing aggregate sizes 14 and 10mm have a good permeability and stability, when vibrated for 65 second with a frequency of 40Hz, while for aggregates containing 20mm, to achieve the requirement for Marshall stability, the gradation needs to be modified. Properties of porous asphalt based on packing theory are better from the empirical grading from Spain (P-12).